Students' Career Attitudes - How Entrepreneurial Are Prospective Scientists? - Nora Hesse (Philipps-University Marburg, Department of Geography, 2015)
The aim of this paper is to find out how entrepreneurial prospective scientists are compared to prospective entrepreneurs. This study investigates the relationship between the intention of students to become scientists or entrepreneurs and their attitudes towards self-realization, recognition, independence, innovation, role models, financial success and social welfare. The study is based on quantitative data from the universities in Hannover and Göttingen which was collected in the context of the Global University Entrepreneurial Spirit Students' Survey. The results of the multinomial and binary logistic regression analyses surprisingly show that prospective scientists in fact are well equipped with attitudes which are conducive for starting a business. Prospective scientists and prospective entrepreneurs both find the realization of their dreams, independency and role models to be more important than other individuals. At the same time, both groups evaluate financial success to be less important than other individuals.
Keywords: L26; 330; career attitude; entrepreneurial intention; prospective entrepreneur; scientist; student survey